Hybrid solar cells - Guenes, Serap; Sariciftci, Niyazi Serdar (ELSEVIER SCIENCE SA, 2008)
Historically, conventional solar cells were built from inorganic materials such as silicon. Although the efficiency of such conventional solar cells is high, very expensive materials and energy intensive processing techniques are required. Hybrid and photoelectrochemical (dye sensitized) solar cells have been the cheap alternatives for conventional silicon solar cells. A hybrid solar cell consists of a combination of both organic and inorganic materials therefore, combines the unique properties of inorganic semiconductors with the film forming properties of the conjugated polymers. Organic materials are inexpensive, easily processable and their functionality can be tailored by molecular design and chemical synthesis. On the other hand, inorganic semiconductors can be manufactured as nanoparticles and inorganic semiconductor nanoparticles other the advantage of having high absorption coefficients and size tunability. By varying the size of the nanoparticles the bandgap can be tuned therefore the absorption range can be tailored. In this short review, we will focus on the concepts of organic/inorganic hybrid'' solar cells. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: organic solar cells; polymer solar cells; nanoporous TiO2; dye-sensitized solar cells; hole transport materials; conjugated polymers; bulk heterojunctions; SOLID-STATE; 3RD-GENERATION PHOTOVOLTAICS; ELECTRON-TRANSFER; TIO2; SEMICONDUCTOR; POLYMER; SENSITIZATION; PHOTOSENSITIZATION; EFFICIENCY; CDSE; Chemistry